A new Neotibicen cicada subspecies (Hemiptera: Cicadidae) from the southeastern USA forms hybrid zones with a widespread relative despite a divergent male calling song - Marshall, David C.; Hill, Kathy B. R. (Zootaxa, 2017)
A morphologically cryptic subspecies of Neotibicen similaris (Smith and Grossbeck) is described from forests of the Apalachicola region of the southeastern United States. Although the new form exhibits a highly distinctive male calling song, it hybridizes extensively where it meets populations of the nominate subspecies in parapatry, by which it is nearly surrounded. This is the first reported example of hybridization between North American nonperiodical cicadas. Acoustic and morphological characters are added to the original description of the nominate subspecies, and illustrations of complex hybrid song phenotypes are presented. The biogeography of N. similaris is discussed in light of historical changes in forest composition on the southeastern Coastal Plain.